Pioneers of photography in Navarre: economic and professional contributions of women in photographic studios and in the publishing and trade of postcards (1861 – 1934) - Agustín-Lacruz, Carmen; García Camón, María Jesús (Revista General de Información y Documentación, 2025)
This study examines the economic and professional contributions of women to the founding and consolidation of the first photographic studios in Navarre. They contributed their own money and labor, both in studios and shops selling photographic products, as well as in the production and sale of postcards, thus facilitating the dissemination of this new photographic medium, its forms of social interaction, and its specific visual culture. The biographies and professional trajectories of these pioneering women, who worked in Pamplona, Tudela, Tafalla and Burguete from the mid-19th century to the early decades of the 20th, are investigated. The research is conducted through a bibliographic review, the compilation and critical analysis of a wide range of archival, newspaper, and documentary sources, many of them previously unpublished. Among the results, the study of figures such as María Eliceche, Urbana de Errazti, Carolina Soler, Juana Juaristi, Ana María Lapetra, Higinia and Casimira Ybarra, Julia Zalba, Emilia Velasco, Serapia Olaverri, Esmeralda Pliego, Blanca Pliego, Isolina Pliego, Ulpiana Laborda, Justa Arozarena, Dominica Cortijo, Avelina Lasheras and Pascuala Echevarría stands out.
Keywords: Women photographers; photographic documentation; photograph; postcards; photography trade; Pamplona; Tudela; Navarra; Hijas de Pliego; Serapia Olaverri